Causal Correlation Between Technology Level, Institutional Support, and Agricultural Extension Role Againts for the Adoption Level of Livestock-Crop Integration - -, Priyono (Informatika Pertanian, 2015)
Efforts to increase the amount of livestock-crop integration adopter needs agricultural extension support and powerful institutional support through technology transfer to farmers. This research was aimed to determine causal correlation between technology level, institutional support and agricultural extension’s role against the adoption level of livestock-crop integration. This research was conducted from 15th February - 31th March 2013 in Sadangkulon, Kebumen Regency. The used method in this study was structured survey method. Respondents were taken as much as 31 people using sample random sampling, as much as 50% from each farmer group. Variables which measured in this study were integration technology level, agricultural extension role, and adoption level of livestock-crop integration. Data were analyzed using path analysis to estimate the coefficient of linear structural equation which has a causal correlation by SPSS tools. The research result showed that the contribution of exogenous variables (technology level, institutional support, and agricultural extension role) simultaneously affecting the adoption level of livestock-crop integration of 72,5% (P < 0,05). Partially, the adoption level of livestock-crop integration was directly affected by the mastery level of technology (16,4%), institutional support (4,7%), and agricultural extension role (13,4%). Based correlation analysis showed that the correlation between exogenous variable have a positive and significant correlation (r12 = 0,580; r13 = 0,703; and r23 = 0,427). Based on the research result, that mastery level of technology, institutional support, and agricultural extension role had a causal correlation against the adoption level of livestock-crop integration.